# Math

posted by .

Factor x^3 - 4x^2 + x + 6 with all steps

• Math -

let f(x) = x^3 - 4x^2 + x + 6
f(1) = 1-4+1+6 ≠0
f(-1) = -1 - 4 -1 + 6 = 0
so (x+1) is a factor

Using synthetic division or long algebraic division
x^3 - 4x^2 + x + 6
= (x+1)(x^2 - 5x + 6)
= (x+1)(x-6)(x+1)

so x = 6 or x = -1 (a double root at x=-1)

• Math -

thank you!

## Similar Questions

1. ### Math

Can somebody please explain to me how to factor trinomials that contain two unknown variables and are complex sum & product?
2. ### math

factor this polynomial function completely f(x)=12x^4+10x^3-214x^2+198x+90 I found all the possible rational zeros but just cant seem to factor it all
3. ### Math

How do you factor "0 = x^4 - 6x^2 + 5"? Please show all steps. Here's my work, but I just went around in circles..... 0 = x^4 - 6x^2 + 5 -5 = x^4 - 6x^2 -5 = x^2 (x^2 - 6) -5 / x^2 = x^2 - 6 (-5 / x^2) + 6 = x^2 (-5 + 6x^2) / (x^2)

Factor f(x) = x^4 + x^3 – 8x^2 + 6x + 36 completely. Show all steps.
5. ### math

If the sides of a box all double in length, by how much does its volume increase?

3. Factor x^4-3x^3-11x^2+3x+10 completely using the factor theorem. (5 marks) SHOW ME ALL THE STEPS PLEASE.